CANVASES OF RESILIENCE: EXAMINING THE EVIDENCE FOR ART THERAPY IN DIVERSE POPULATIONS AND SETTINGS FOR CHILDREN AND ADOLESCENTS - Mohd Imran Yusoff; Nor Shafrin Ahmad, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This Systematic Literature Review (SLR) aims to uncover how art therapy interventions can be useful in enhancing the quality of life of children and adolescents. In this study, 31 papers are included from the Scopus and Web of Science (WoS) databases from the year 2020 to 2024 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The findings are organized into three main themes: (1) the art therapy’s effectiveness in managing emotional, behavioral, and psychological issues, (2) the application of art therapy for specific populations and settings, and (3) the multiple art therapy approaches, strategies, and assessments that were incorporated in the most recent research. The findings also indicate that art therapy interventions enhance the regulation of emotions, lessen aggression and disruptive conduct, and promote self-esteem and life in clients in different settings. The review also shows case and context specificity in the implementation of art therapy interventions for children with particular conditions and disorders. In addition, the creation and calibration of the measurement instruments also support the growth of evidence-based practice in art therapy. However, the review also points out some research limitations that need to be addressed in future studies, such as small sample sizes, short follow-up periods, and comparison with other evidence-based treatments. Thus, the SLR concludes with specific recommendations for future research and practice, marked by the necessity for more methodologically sound studies, defining the processes that contribute to art therapy effectiveness, and enhancing the accessibility of evidence-based art therapy practices.